Tax Incentives and Investment in the Eastern Caribbean - Sosa, Sebastian (IMF Working Papers; Working Paper ;, 2006)
Tax incentives have been used extensively in the countries of the Eastern Caribbean Currency Union (ECCU) to promote investment. The associated revenue losses are large, and benefits in terms of new investment have been limited, raising doubts about the cost effectiveness of the tax incentive schemes. This paper examines the effects of incentives using the marginal effective tax rate approach (METR), adapting this methodology to the case of a small open economy where the marginal investor is a nonresident. The results show that METRs are high in the region; that there is a large dispersion in the size of METRs across financing source; and that METRs on investment are larger than the overall distortion on capital, with a substantial subsidy to domestic saving. In the presence of tax holidays-the most common incentive scheme in the region-the distortion on capital basically vanishes.